Interspecific diversity in root antioxidative enzyme activities reflect root turnover strategies and preferred habitats in wetland graminoids. Issue 6 (20th February 2014) - Yücel, Çağdaş Kera; Bor, Melike; Ryser, Peter
Abstract Antioxidant enzymes protect cells against oxidative stress and are associated with stress tolerance and longevity. In animals, variation in their activities has been shown to relate to species ecology, but in plants, comparative studies with wild species are rare. We investigated activities of five antioxidant enzymes – ascorbate peroxidase (APX), catalase (CAT), glutathione reductase (GR), peroxidase (POX), and superoxide dismutase (SOD) – in roots of four perennial graminoid wetland species over a growing season to find out whether differences in root turnover or habitat preferences would be associated with variation in seasonal patterns of antioxidant enzyme activities. The investigated species differ in their root turnover strategies (fine roots senesce in the fall or fine roots survive the winter) and habitat preferences (nutrient‐poor vs. productive wetlands). Roots were collected both in the field and from garden‐grown plants. Antioxidant enzyme activities were higher and lipid peroxidation rates lower in species with annual root systems, and for species of the nutrient‐poor wetland, compared with perennial roots and species of productive wetlands, respectively. There was variation in the activities of individual antioxidant enzymes, but discriminant analyses with all enzymes revealed a clear picture, indicating consistent associations of antioxidant enzyme activities with the type of root turnover strategy and with the preferred habitat. We conclude that antioxidant enzyme activities in plant roots are associated with the species' ecological strategies and can be used as traits for the characterization of the species' position along plant economics spectrum.